All-fiber all-normal-dispersion passively mode-locked Yb-doped ring laser based on graphene oxide - Li, Xiaohui (2013)
We demonstrate an all-fiber all-normal-dispersion Yb-doped fiber laser that is passively mode locked by a graphene oxide (GO)-polymer. Because of good solution processing characteristic of the GO to polymer, a GO-polymer saturable absorber (SA) was successfully fabricated. Self-started mode-locking laser performance was investigated comprehensively at different cavity lengths, from 5, 24, to 94 m. The results showed that the pulse duration varies from hundreds of picoseconds to nanoseconds. In addition, the average output power of the mode-locked fiber laser can reach up to 500 mW. Furthermore, it was demonstrated that pulses with large chirps can be more easily amplified to reach high output power.